Cesarean scar pregnancy: Reproductive outcome after robotic laparoscopic removal with simultaneous repair of the uterine defect. (July 2021) - Hofgaard, Ellen; Westman, Katarina; Brunes, Malin; Bossmar, Thomas; Persson, Jan
Highlights: Robotic removal with simultaneous repair is a safe option for early CSP. Immediate removal and repair should be offered to women with CSP during counseling. Fertility rates following the procedure are encouraging. Abstract: Objective: To describe perioperative adverse events, fertility and obstetric outcome, following a robot assisted laparoscopic approach for treating Cesarean scar pregnancies (CSP). Study Design: A retrospective case series of 14 consecutive women with a CSP and a wish for and attempts towards subsequent pregnancies, having undergone minimal invasive surgical treatment at two tertiary referral Swedish centers (Dep's of Obstetrics and Gynecology Skåne University Hospital, Lund, and Södersjukhuset, Stockholm) between 2008 and 2019. The surgery was performed by temporary intraoperative occlusion of the uterine blood supply, removal of the CSP and repair of the niche, by the use of robot assisted laparoscopy (Da Vinci surgical robot, Intuitive Surgical, Sunnyvale, CA). Results: All surgeries were uneventful with a median bleeding of 75 mL. One woman had a postoperative Clavien-Dindo complication grade IIIa (hysteroscopic resection of an isthmic synechiae). During follow up nine women (64 %) conceived naturally; eight of these had an uneventful pregnancy and a full-term Cesarean delivery and one had recurrent CSP and Cesarean with simultaneous hysterectomy in gestational week 33. Conclusion: A robotic removal of a CSP with simultaneous repair of the defect is a feasible option with acceptable reproductive outcome and should be considered when counseling women with a wish for future childbirth in cases of a live CSP and a thin, or absent, myometrium in the niche. A temporary intraoperative occlusion of the uterine blood supply may be useful in cases of live pregnancies and/or high serum β-hCG levels.